The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1029/2002gl015867
|View full text |Cite
|
Sign up to set email alerts
|

The Northeastward current southeast of Okinawa Island observed during November 2000 to August 2001

Abstract: In order to estimate the variability of current structure and mean geostrophic volume transport in the southeast of Okinawa Island, the round‐trip acoustic travel times between sea bottom and surface at nine sites were measured by Inverted Echo Sounder with pressure gauge (PIES) from November 2000 to August 2001. Vertical sections of geostrophic velocity are calculated by using vertical profiles of specific volume anomaly derived by the Gravest Empirical Mode method from the PIES data. In the upper 500 m layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 8 publications
(9 reference statements)
0
41
2
Order By: Relevance
“…These conclusions suggest that the RCS observed to the southeast of Amami-Ohshima Island should be a continuation of the Kuroshio Branch Current east of Taiwan. However, Zhu et al (2003) The distribution of 5-year mean stream function from 1996 to 2001 estimated from the result of a data assimilating numerical model calculation by Kamachi et al (2004) is shown in Fig. 16, in which the southwestern edge of the Kuroshio recirculation gyre reaches to the south of Okinawa Island, suggesting that the main part of RCS does not originate from the Kuroshio Branch Current east of Taiwan but the westward Kuroshio recirculation flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conclusions suggest that the RCS observed to the southeast of Amami-Ohshima Island should be a continuation of the Kuroshio Branch Current east of Taiwan. However, Zhu et al (2003) The distribution of 5-year mean stream function from 1996 to 2001 estimated from the result of a data assimilating numerical model calculation by Kamachi et al (2004) is shown in Fig. 16, in which the southwestern edge of the Kuroshio recirculation gyre reaches to the south of Okinawa Island, suggesting that the main part of RCS does not originate from the Kuroshio Branch Current east of Taiwan but the westward Kuroshio recirculation flow.…”
Section: Discussionmentioning
confidence: 99%
“…The interannual signal of TVT has two maxima in April of 1999 and 2001, and one minimum in March 2000 with a variation range of 5 Sv, suggesting the existence of a quasi-biennial oscillation in TVT corresponding to the variation of SVT or SSAGC. The annual signal of TVT has a maximum in summer (July 1999, August 2000, September 2001) and a minimum in the late winter (February 1999, March 2000, March 2001, February 2002. It should be emphasized that the variation ranges of interannual and annual signals are nearly equal.…”
Section: Volume Transport Between 2745 and 2790°nmentioning
confidence: 99%
“…At the latitudes of the East China Sea, the strongest transport variability is within the Ryukyu Current along the southeastern side of the Ryukyu Islands (Figure 1a, red dashed line), which is directly exposed to eddies arriving from the ocean interior (Zhu et al, 2003;Andres et al, 2008a). However, there is also Kuroshio transport variability within the East China Sea (at the PN Line) that is driven by these eddy arrivals outside of the island chain (Andres et al, 2008a).…”
Section: Connectivity Along the Kuroshiomentioning
confidence: 99%
“…Integrating over the regions of contiguous positive velocity (i.e., the red shaded areas in the sections shown in Figure 3b-d) indicates that the Kuroshio strengthens from a mean downstream transport of about 15 Sv east of Luzon to 24 ± 0.9 Sv in the East China Sea. The Kuroshio further strengthens to 65 ± 6 Sv at the ASUKA Line, fed in part by the Ryukyu Current (Zhu et al, 2003), a subsurface intensified current that flows along the southwestern side of the Ryukyu Islands and joins the Kuroshio as it exits the East China Sea through Tokara Strait (indicated with the red dashed line in Figure 1a). (Transport values are based on HPIES and ADCP data collected east of Luzon [Lien et al, 2014, and this issue], Andres et al [2008b], and Book et al [2002], with the ASUKA Line mean calculated over two years rather than from the 153-day mean sections shown in Figure 3d.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation